USING OPERATION TECHNIQUE TO TEACH SPEAKING OF PROCEDURE TEXT - Darmadi, Hamid; Sudarsono, Sudarsono; Regina, Regina (IKIP PGRI Pontianak, 2019)
The research was aimed to examine the operation technique to improve teaching speaking in a procedure text. The research was Classroom Action Research in three cycles. The participants of the research were year 11 students of SMK Al-Madani Pontianak who had difficulties in speaking skills, especially in performing spoken texts in a procedure text. The data were divided into qualitative and quantitative data. The qualitative data were collected by using questionnaires, video recordings, observation sheets, observation’s checklists, student’s self-evaluation, and field notes. Meanwhile, the quantitative data were collected from the student’s performance tests. The finding showed that through operation, the student’s learning behavior changed positively from less to good. The writer concludes that the use of operation technique which is adjusted to the classroom’s condition improve teaching speaking in a procedure text as well as the student’s speaking skill in performing the procedure text.